2021
DOI: 10.1007/s42399-021-01014-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Treatment Efficacy and Safety of Remdesivir for COVID-19: a Meta-analysis

Abstract: Remdesivir is one of few FDA-approved treatments for severe cases of Coronavirus Disease 2019 (COVID-19). To better assess its efficacy and safety, we conducted a meta-analysis to systematically identify and synthesize existing findings. We conducted a comprehensive literature search among six electronic databases and unpublished studies. Random-effects meta-analyses were performed to summarize the risk ratio (RR) and rate estimates from eligible studies. Funnel plots, the Egger test, and the trim and fill ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Additionally, a genotyping assay may have utility to distinguish between persistent infection with the same viral strain vs. reinfection due to a new strain in an individual with recurrent positive molecular test results for SARS-CoV-2. Finally, a genotyping assay could be designed to detect select variants in the spike (S), RdRp polymerase, or the nsp5 protease coding regions associated with reduced efficacy to therapeutics including spike-targeting monoclonal antibodies ( Kreuzberger et al., 2021 ), polymerase inhibitors such as remdesivir ( Tao et al., 2021a ) and molnupiravir ( Pourkarim et al., 2022 ), and protease inhibitors such as nirmatrelvir ( Vangeel et al., 2022 ). An RT-PCR genotyping assay may be performed in a high-throughput manner and at a lower cost than WGS.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a genotyping assay may have utility to distinguish between persistent infection with the same viral strain vs. reinfection due to a new strain in an individual with recurrent positive molecular test results for SARS-CoV-2. Finally, a genotyping assay could be designed to detect select variants in the spike (S), RdRp polymerase, or the nsp5 protease coding regions associated with reduced efficacy to therapeutics including spike-targeting monoclonal antibodies ( Kreuzberger et al., 2021 ), polymerase inhibitors such as remdesivir ( Tao et al., 2021a ) and molnupiravir ( Pourkarim et al., 2022 ), and protease inhibitors such as nirmatrelvir ( Vangeel et al., 2022 ). An RT-PCR genotyping assay may be performed in a high-throughput manner and at a lower cost than WGS.…”
Section: Discussionmentioning
confidence: 99%
“… 19 According to a meta-analysis, a substantial number of patients (20–30%) has been reported to exhibit serious adverse events or Grade 3 or 4 adverse events during the course of the treatment with remdesivir. 22 Another systematic review and meta-analysis indicated that remdesivir showed neither benefit against all-cause mortality nor significant treatment efficacy in COVID-19 patients in comparison to placebo/ no treatment groups. Rather patients treated with remdesivir revealed increased risk of nausea than no treatment/placebo groups.…”
Section: Discussionmentioning
confidence: 99%
“…It is actually a phosphoramidate prodrug having broad-spectrum activity against various viruses, for example, Paramyxoviridae, Filoviridae, Pneumoviridae, and Orthocoronavirinae, that is, SARS-CoV and Middle East respiratory syndrome coronavirus (MERS-CoV), as described elsewhere (Sheahan et al, 2017;Martinez, 2020;Gavriatopoulou et al, 2021). Although the FDA has recommended emergency use of RDV in severe COVID-19 patients, however, the safety and efficacy of RDV in COVID-19 patients as evidenced in multiple recent meta-analyses are controversial and inconsistent (Angamo et al, 2021;Elsawah et al, 2021;Tao et al, 2021).…”
Section: Repurposing Drugs For Covid-19: Concept and Mechanism Of Actionmentioning
confidence: 99%